Walnut shell photo-thermal conversion method based on molecular sieve coupling nanometer zero-valent iron
By using molecular sieve coupled nano zero-valent iron catalyst on walnut shells for photothermal reaction, the problems of low energy efficiency, high pollution and poor performance in walnut shell resource utilization technology are solved, and the efficient and environmentally friendly walnut shells are converted into high-value-added phenol and porous carbon materials are achieved.
Patent Information
- Application Number
- CN202510361420.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-03-26
- Publication Date
- 2025-06-17
AI Technical Summary
The existing walnut shell resource utilization technology has problems such as low energy efficiency, high pollution and poor performance, which limits its large-scale application and promotion.
A catalyst based on molecular sieve-coupled nano-zero-valent iron is used to convert walnut shells into phenolic substances, especially phenol, through photothermal reaction, with a selectivity of more than 90%, and a porous carbon material is generated.
High-efficiency photothermal conversion of walnut shells is achieved, the proportion of phenolic substances in the product is not less than 40%, the phenol selectivity is high, the yield of porous adsorbent materials reaches more than 35%, and the catalytic system shows excellent thermodynamic stability.
Smart Images

Figure CN120155442A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of biomass resource utilization, and particularly relates to a method for photothermal conversion of walnut shells based on the coupling of molecular sieves and nano zero-valent iron. Background Art
[0002] As an important cash crop, walnuts have a large industrial scale and increasing annual output. According to relevant statistics, the global annual walnut output has exceeded ten million tons. During the walnut processing, a large amount of walnut shell waste is generated, and its output accounts for about 50% of the total walnut output. If these walnut shell wastes are not properly treated, they will not only occupy a large amount of land resources but also cause serious environmental pollution. Traditional treatment methods such as landfill and incineration not only waste the rich organic carbon resources contained in walnut shells but also cause problems such as greenhouse gas emissions.
[0003] Currently, the main walnut shell resource utilization technologies include converting walnut shells into carbon materials with specific properties (such as carbon nanotubes, activated carbon, hard carbon materials, etc.) through pyrolysis reactions, and preparing syngas (CO and H2). For example, Chinese Patent CN119370832A provides a method for preparing a CNTs@C core-shell structure hydrogen storage material, which grows carbon nanotubes on the carbon-based surface through steps such as biomass carbonization, resin compounding, and high-temperature reduction to enhance hydrogen storage performance. However, this technology has significant environmental drawbacks: during the preparation process, a hydrochloric acid etching process is used to treat the carbonization raw materials, generating a large amount of high-concentration acidic waste liquid, and there is no integrated waste liquid recycling and purification or neutralization treatment device, which is likely to cause environmental pollution; in addition, the high-temperature calcination stage relies on a reducing atmosphere (such as a hydrogen / argon mixed gas), and there is no tail gas recovery system, which may increase the risk of energy consumption and greenhouse gas emissions. The green degree of the overall process is insufficient, restricting its potential for sustainable application. In addition, converting walnut shells into syngas through gasification reactions, the main components of which are carbon monoxide and hydrogen. Chinese Patent CN119193955A introduces a method for preparing syngas using biomass gasification. This method uses a fluidized bed reactor to react biomass with a gasifying agent under high temperature and anoxic conditions to generate syngas rich in carbon monoxide and hydrogen, which can be further synthesized into liquid fuels or other chemicals as chemical raw materials. However, gasification technology also requires high energy consumption and strict control of reaction conditions; otherwise, it will affect the quality and yield of syngas.
[0004] Existing walnut shell resource utilization technologies have problems such as high energy consumption, high carbon emissions, and the need to improve economic value, which limit their large-scale application and promotion. As an emerging catalytic technology, photothermal catalytic technology has received extensive attention in recent years. It combines the advantages of photocatalysis and thermocatalysis, can utilize the full spectrum of light in the solar spectrum, including ultraviolet light, visible light, and near-infrared light, and convert light energy into heat energy and chemical energy, thereby improving the reaction efficiency and energy utilization efficiency. Photothermal catalytic technology can directly use solar energy as the driving force for the reaction, reduce dependence on traditional energy sources, and reduce energy consumption and greenhouse gas emissions. In addition, the photothermal effect can enhance the activity of the catalyst, promote the activation of reactant molecules and the progress of the reaction, and improve the reaction rate and product selectivity. The carbon dioxide emissions generated during the reaction are significantly reduced, which helps to slow down global climate change and meets the national dual-carbon policy goals.
[0005] At present, certain research progress has been made in the field of biomass conversion using photothermal catalytic technology. For example, it shows good application prospects in the preparation of cellulose photothermal membranes (CN118085357A), cellulose photothermal hydrogels (CN119570064A), etc. However, the photothermal catalytic resource utilization research on whole biomass, especially walnut shells, is still in its infancy, and no mature patented technology has emerged yet. Therefore, developing a catalyst for the photothermal conversion of walnut shells and thus developing a new type of walnut shell photothermal resource utilization technology is of great significance for improving the resource utilization efficiency of walnut shells, reducing environmental pollution, and promoting sustainable development. Summary of the Invention
[0006] The purpose of the present invention is to provide a walnut shell photothermal conversion method based on zeolite-coupled nano-zero-valent iron to solve at least one of the above problems, and to solve the bottleneck problems of low energy efficiency, high pollution, and poor performance in the resource utilization of biomass (especially walnut shells) in the prior art. This technical solution realizes the zero-carbon resource utilization of walnut shells into phenolic substances through photothermal conversion, with a phenol selectivity exceeding 90%. The catalyst for the photothermal conversion of walnut shells realizes the conversion of walnut shells into high-value phenolic chemicals and porous carbon materials by regulating the surface acid-base characteristics and energy band structure of the material.
[0007] The purpose of the present invention is achieved through the following technical solutions:
[0008] A walnut shell photothermal conversion method based on zeolite-coupled nano-zero-valent iron includes the following steps:
[0009] Grind and mix the zeolite-coupled nano-zero-valent iron catalyst with walnut shells evenly, then spread them flat in a photothermal reactor, and carry out a photothermal reaction under a protective atmosphere to perform photothermal conversion on the walnut shells and produce phenolic substances;
[0010] Among them, the molecular sieve-coupled nano-zero-valent iron catalyst is: a micron-sized molecular sieve loaded with nano-zero-valent iron particles.
[0011] Preferably, in the molecular sieve-coupled nano-zero-valent iron catalyst:
[0012] The size of the micron-sized molecular sieve is 0.5 - 3 μm, and the particle size of the nano-zero-valent iron particles is 1 - 1000 nm.
[0013] Preferably, the molecular sieve-coupled nano-zero-valent iron catalyst is prepared by the following steps:
[0014] S1: Add an iron source and micron-sized molecular sieve powder to deionized water to form a suspension;
[0015] S2: Under ultrasonic conditions, drop a NaBH4 solution into the suspension, and then carry out aging;
[0016] S3: Separate the solid product obtained from the reaction, wash and dry it to obtain the molecular sieve-coupled nano-zero-valent iron catalyst.
[0017] Preferably, in step S1,
[0018] The mass ratio of the iron source to the micron-sized molecular sieve is 0.1 - 10:1;
[0019] The iron source is a soluble iron-containing compound, including FeCl3, FeCl2, Fe(NO)3, Fe(NO)2, etc. and their corresponding hydrates, and the micron-sized molecular sieve is a 4A molecular sieve with 200 - 400 mesh.
[0020] Preferably, in step S2,
[0021] The mass ratio of NaBH4 in the NaBH4 solution to the iron source in the suspension is 1.5 - 5:1;
[0022] The aging time is 2 - 5 hours.
[0023] Preferably, in step S3,
[0024] The separation is suction filtration;
[0025] The washing is successively carried out with deionized water and ethanol;
[0026] The drying is vacuum freeze-drying, and the drying time is 12 - 18 h.
[0027] Preferably,
[0028] The mass ratio of the molecular sieve-coupled nano-zero-valent iron catalyst to walnut shell is 1:2.5 - 3;
[0029] The walnut shell is 100-150 mesh, and the walnut shell is selected from one or more of Persian walnut shell, iron walnut shell, black walnut shell and hickory shell.
[0030] Preferably, deionized water is also added during the grinding process, and the mass ratio of the deionized water to the walnut shell is 0.5:2.5-3.
[0031] Preferably, the protective atmosphere is nitrogen, argon or steam atmosphere.
[0032] Preferably, the photothermal reaction uses a xenon lamp light source to irradiate the mixture, and the light intensity is 0.1-6.0 W·cm -2 , so that the reaction temperature reaches above 250 °C, and the reaction time is 20-150 minutes.
[0033] The working principle of the present invention is as follows:
[0034] The present invention proposes a walnut shell directional conversion technology based on a molecular sieve / zero-valent iron heterostructure, which realizes the conversion of walnut shell into high-value phenol chemicals and porous carbon materials by precisely regulating the size of nano zero-valent iron and the acid sites of the molecular sieve. Among them, 1-1000 nm zero-valent iron nanoparticles exhibit 300-2500 nm ultra-wideband light response characteristics, and their local surface plasmon resonance effect can convert the full-spectrum sunlight into a nano-scale thermal field, convert light energy into heat energy and carriers, and simultaneously transfer them to the molecular sieve to drive the resource-based reaction of walnut shell. Nano zero-valent iron coupled with the molecular sieve has specific acid sites, which can promote the efficient bond breaking and recombination of C-C / H bonds in the walnut shell and O-H bonds in water through carbocation intermediates and control the degree of chemical bond breaking, generating high-value phenol chemicals and porous adsorption materials (such as porous adsorption material solid carbon, etc., which can be applied to the removal of gas or liquid pollutants, such as removing gas VOC such as formaldehyde and heavy metal pollutants in wastewater).
[0035] Compared with the prior art, the present invention has the following beneficial effects:
[0036] (1) Through the construction of a catalytic system coupling molecular sieve and zero-valent iron, this technical solution realizes the directional conversion of walnut shell biomass under the synergistic action of photothermal. In the product system, the proportion of phenolic products is not less than 40%, the selectivity of phenol is not less than 90%, the yield of porous adsorption materials reaches more than 35%, and the catalytic system exhibits excellent thermodynamic stability;
[0037] (2) An innovative catalytic system with photocatalytic response characteristics to the full solar spectrum (200 - 2300 nm) was constructed. This system can operate continuously and stably under natural light conditions, and through the photothermal catalytic reaction, the synchronous preparation of high - value - added chemicals and porous adsorption materials from walnut shell waste was realized;
[0038] (3) By means of interface engineering, the surface acid - base properties and energy band structure of the catalytic material were regulated, and the generation rate and product distribution selectivity of the target product phenol were significantly improved without reducing the light energy utilization efficiency;
[0039] (4) This technology has created a new model for the circular utilization of biomass resources, constructed a new type of (biomass) waste regeneration process route with low carbon emissions, economic environmental protection, and industrialization potential, and achieved triple synergistic benefits of pollutant treatment, carbon emission reduction, and resource regeneration;
[0040] (5) The developed catalytic system has good environmental compatibility, no harmful by - products are generated during use, and it still maintains its main catalytic performance after regeneration treatment;
[0041] (6) The preparation technology of this catalyst uses conventional chemical raw materials, and the construction of the catalyst can be completed through a simple wet synthesis process. The entire process does not require special equipment or strict operating conditions, and has significant industrial application advantages. Description of the Drawings
[0042] Figure 1 SEM image of the zeolite - coupled nano - zero - valent iron synthesized in Example 1;
[0043] Figure 2 TEM image of the zeolite - coupled nano - zero - valent iron synthesized in Example 1;
[0044] Figure 3 XRD patterns of the zeolite - coupled nano - zero - valent iron and pure zeolite synthesized in Example 1;
[0045] Figure 4 NH₃ - temperature - programmed desorption diagrams of the zeolite - coupled nano - zero - valent iron and pure zeolite synthesized in Example 1;
[0046] Figure 5 Photocatalytic response characteristics diagram of the zeolite - coupled nano - zero - valent iron synthesized in Example 1;
[0047] Figure 6 Total ion intensity diagram of the GC - MS of the pyrolysis products of walnut shells in Example 2;
[0048] Figure 7 Total ion intensity diagram of the GC - MS of the pyrolysis products of walnut shells in Control Example 1;
[0049] Figure 8It is the total ion intensity chromatogram of the pyrolysis products of walnut shell in Comparative Example 2. Detailed implementation mode
[0050] The present invention will be described in detail below with reference to the accompanying drawings and specific embodiments. Obviously, the described embodiments are only used to clarify the technical solutions of the present invention, not all embodiments. All other embodiments obtained by those of ordinary skill in the art based on the embodiments of the present invention without creative work are still within the protection scope of the present invention.
[0051] In the following description, if not otherwise specified, the reagents used are conventional commercially available products, the methods used are common knowledge in the art, and the matters not covered can adopt the existing technologies.
[0052] Aiming at the problems commonly existing in the field of high-value conversion of biomass, such as low energy efficiency in the treatment process and insufficient pollution control, especially the research gap in the direction of photothermal synergistic conversion technology of agricultural and forestry waste represented by walnut shells, the present invention proposes a method for photothermal catalytic conversion of walnut shells.
[0053] This technical solution is realized through the following innovative paths: Select a transition metal iron-coupled molecular sieve material with a micro-nano structure as the photothermal reaction catalyst. In a pure light-driven reaction system without external heat energy input, use the photothermal synergistic catalytic mechanism to achieve the selective depolymerization of walnut shell biomass. This process realizes the directional conversion of biomass components into two high-value products, namely high-purity phenol and environmental remediation carbon materials, by precisely regulating the coupling path of light-thermal-chemical energy. Through the optimization of the micro-region morphology and surface regulation of the catalyst, the ability of the system to capture photons and the activation efficiency of catalytic sites can be significantly enhanced, further improving the conversion rate of walnut shells to target products and the product purity.
[0054] Specifically, the present invention provides a method for photothermal catalytic conversion of walnut shells, including the following steps:
[0055] Take 1 part by mass of the molecular sieve-coupled nano-zero-valent iron catalyst, 0.5 part by mass of deionized water and 2.5 - 3 parts by mass of walnut shell powder, grind and mix them evenly, then spread them flat in a photothermal reactor. Pass a protective gas into the photothermal reactor to exhaust air, irradiate the mixture of the catalyst and walnut shell with a xenon lamp light source, measure the temperature with a thermocouple above 250 °C, and carry out the photothermal reaction for more than 20 minutes;
[0056] Among them,
[0057] For the molecular sieve-coupled nano-zero-valent iron catalyst, nano-zero-valent iron particles are attached to the surface of the molecular sieve, where the size of the molecular sieve is between 0.5 - 3 μm, and the nano-zero-valent iron particles are between 1 - 1000 nm.
[0058] Preferably, the molecular sieve-coupled nano zero-valent iron catalyst is prepared by the following steps:
[0059] An iron source and micron-sized molecular sieve powder are added to deionized water to form a suspension; under ultrasonic conditions, a NaBH4 solution is dropped into the suspension, followed by aging; the solid product obtained from the reaction is separated, washed, and dried to obtain the molecular sieve-coupled nano zero-valent iron catalyst.
[0060] Preferably, the mass ratio of the iron source to the micron-sized molecular sieve is 0.1-10:1; the iron source is a soluble iron-containing compound, including FeCl3, FeCl2, Fe(NO)3, Fe(NO)2, etc. and their corresponding hydrates, and the micron-sized molecular sieve is a 4A molecular sieve with a mesh size of 200-400.
[0061] Preferably, the mass ratio of NaBH4 in the NaBH4 solution to the iron source in the suspension is 1.5-5:1; the aging time is 2-5 hours.
[0062] Preferably, the separation is carried out by suction filtration; the washing is carried out by washing successively with deionized water and ethanol; the drying is carried out by vacuum freeze-drying, and the drying time is 12-18h.
[0063] More preferably, the molecular sieve-coupled nano zero-valent iron catalyst is prepared by the following steps:
[0064] 3 g of FeCl3·6H2O and 3 g of 4A molecular sieve powder are added to 1000 mL of deionized water to form a suspension; 6 g of NaBH4 is added to 400 mL of deionized water to form a NaBH4 solution;
[0065] Under ultrasonic conditions, the NaBH4 solution is slowly dropped into the suspension, and black solids appear in the mixed liquid; after the NaBH4 solution is completely dropped, it is aged for 2.0 hours;
[0066] The whole liquid is subjected to suction filtration, and the solid product obtained after suction filtration is washed three times with 100 mL of deionized water and then twice with 80 mL of ethanol;
[0067] It is freeze-dried in vacuum for 15 h to dry the solid. After slowly restoring to room temperature, the molecular sieve-coupled nano zero-valent iron catalyst is obtained.
[0068] After slowly restoring to room temperature, the nano zero-valent iron catalyst is obtained.
[0069] Preferably, the powder of the 4A molecular sieve is between 200 and 400 meshes.
[0070] Preferably, the walnut shell powder is between 100 and 150 mesh.
[0071] Preferably, the illumination intensity of the xenon light source is between 0.1 W·cm -2 and 6.0 W·cm -2 .
[0072] Preferably, the time of the photothermal reaction is between 20 and 150 minutes.
[0073] Preferably, the protective gas is nitrogen, argon or water vapor.
[0074] Preferably, in the reaction product, the proportion of phenolic products is not less than 40%, the selectivity of phenol is not less than 90%, and the proportion of the environmental remediation material is not less than 35%.
[0075] Preferably, the walnut shell includes any one or more of but not limited to Persian walnut shell, iron walnut shell, black walnut shell, and hickory shell.
[0076] Example 1: Preparation of molecular sieve coupled with nano-zero valent iron
[0077] 3 g of FeCl3·6H2O and 3 g of 300-mesh 4A molecular sieve powder were added to 1000 mL of deionized water to form a suspension.
[0078] 6 g of NaBH4 was added to 400 mL of deionized water to form a NaBH4 solution.
[0079] Under ultrasonic conditions, the prepared NaBH4 solution was slowly dropped into the prepared suspension, and black solids would appear in the mixed liquid; after the NaBH4 solution was completely dropped, it was aged for 2.0 hours.
[0080] The whole liquid was filtered by suction. The solid product obtained after suction filtration was washed three times with 100 mL of deionized water and then twice with 80 mL of ethanol;
[0081] It was freeze-dried under vacuum for 15 h to dry the solid; after slowly restoring to room temperature, the molecular sieve coupled nano-zero valent iron catalyst was obtained.
[0082] The nano-zero valent iron particles are attached to the surface of the molecular sieve, where the size of the molecular sieve is between 0.5 and 3 μm, and the size of the nano-zero valent iron particles is between 30 and 100 nm.
[0083] Figure 1 It is the SEM image of the molecular sieve coupled nano-zero valent iron catalyst. It can be seen from the figure that the nano-zero valent iron particles are attached to the surface of the molecular sieve, where the size of the molecular sieve is between 0.5 and 3 μm, and the size of the nano-zero valent iron particles is between 30 and 100 nm. Figure 2It is the TEM image of the molecular sieve coupled with nano-zero valent iron catalyst. It can be seen from the figure that the nano-zero valent iron particles are successfully coupled with the molecular sieve. Figure 3 It is the XRD pattern of the nano-zero valent iron coupled with molecular sieve material, which shows that the addition of nano-zero valent iron does not significantly change the lattice characteristics of the molecular sieve. Figure 4 It is the NH₃ temperature-programmed desorption diagram of the molecular sieve coupled with nano-zero valent iron material, indicating that compared with pure 4A molecular sieve, the molecular sieve coupled with nano-zero valent iron material has unique acidic sites. Figure 5 The response characteristics of the molecular sieve coupled with nano-zero valent iron material prepared in this example to light of different wavelengths are shown. It can be seen that it has a light response under the full solar spectrum of 200 - 2300 nm. Therefore, this catalyst can operate continuously and stably under natural light conditions.
[0084] Example 2: Photothermal conversion of walnut shell under argon atmosphere
[0085] 100 mg of the molecular sieve coupled with nano-zero valent iron catalyst prepared in Example 1, 50 mg of deionized water and 250 mg of 150-mesh walnut shell powder were ground and mixed evenly, and then spread out in the photothermal reactor.
[0086] Argon was introduced into the photothermal reactor for 10 min to exhaust the air.
[0087] Using a xenon lamp source with a light intensity of 4.0 W·cm -2 The mixture of the catalyst and walnut shell was irradiated with the xenon lamp of the above light intensity. The temperature measured by the thermocouple exceeded 300 °C within 10 minutes, and the reaction was carried out for 1 hour.
[0088] The remaining solid after the reaction was collected, weighed, and the yield of the environmental functional treatment material was calculated to be 35%.
[0089] In the examples and comparative examples of the present invention, we used a gas chromatography-mass spectrometry (GC-MS) to analyze the products generated by the photothermal cracking of walnut shell in detail. Through GC-MS, we can comprehensively evaluate the cracking products of lignin under photothermal catalysis. The total ion current chromatogram obtained in Example 2 shows the types and contents of the products in detail, as Figure 6 shown, and the calculated phenol selectivity is 92%.
[0090] Comparative Example 1: Photothermal conversion experiment of walnut shell using pure 4A molecular sieve
[0091] 100 mg of 4A molecular sieve, 50 mg of deionized water and 250 mg of walnut shell powder were ground and mixed evenly, and then spread out in the photothermal reactor. Argon was introduced into the photothermal reactor for 10 min to exhaust the air. Using a xenon lamp source with a light intensity of 4.0 W·cm -2Irradiate the mixture of the aforementioned catalyst and walnut shell with xenon lamp light of a certain light intensity. The temperature measured by the thermocouple exceeds 300 °C within 10 minutes, and the reaction can be carried out for 1 hour.
[0092] Collect the remaining solid after the reaction, weigh it, and calculate the yield of the porous adsorbent material to be 26%.
[0093] The total ion current chromatogram of GC-MS obtained in Comparative Example 1 is as Figure 7 shown, and the calculated phenol selectivity is 14%. It can be seen that compared with the pure 4A molecular sieve method, the molecular sieve coupled with nano-zero valent iron material can greatly improve the product selectivity and reduce the generation of by-products; at the same time, it can produce more environmentally functional carbon materials. Therefore, the photothermal method has greater advantages in resource utilization and environmental protection.
[0094] Comparative Example 2: This method is a control experiment with the existing pyrolysis
[0095] To illustrate the advantages of the photothermal method for cracking walnut shells provided by the embodiments of the present invention, a pure pyrolysis control experiment was carried out at the same temperature (350 °C);
[0096] After grinding and mixing 100 mg of the molecular sieve coupled with nano-zero valent iron material, 50 mg of deionized water and 250 mg of walnut shell powder evenly, spread them out in the reactor. Argon gas was passed through the reactor for 10 min to exhaust the air. The mixture was heated to 350 °C using a heating device, and the heating was stopped after 1 hour of reaction.
[0097] Collect the remaining solid after the reaction, weigh it, and calculate the yield of the porous adsorbent material to be 10%.
[0098] The total ion current chromatogram of GC-MS obtained in Comparative Example 2 is as Figure 8 shown, and the calculated phenol selectivity is 52%. The experimental data show that the photothermal catalytic technology shows significant advantages in product regulation compared with the traditional cracking process, not only effectively improving the yield of the target product, but also significantly inhibiting the generation of by-products and simultaneously promoting the formation of ecological functional carbon-based materials.
[0099] In summary, this technology shows better technical economy in improving the conversion efficiency of biomass resources and strengthening pollution control.
[0100] Example 3
[0101] This example is basically the same as Example 1, and the main difference is that when preparing the suspension, 6 g of Fe(NO)3·9H2O and 3 g of 400-mesh 4A molecular sieve powder are added to 1000 mL of deionized water; correspondingly, when preparing the NaBH4 solution, 9 g of NaBH4 is added to 400 mL of deionized water.
[0102] The prepared product is basically the same as that of Example 1 and will not be elaborated here.
[0103] Example 4
[0104] This example is basically the same as Example 1. The main difference is that when preparing the suspension, 2 g of FeCl2·4H2O and 4 g of 200-mesh 4A molecular sieve powder are added to 1000 mL of deionized water; correspondingly, when preparing the NaBH4 solution, 10 g of NaBH4 is added to 400 mL of deionized water.
[0105] The prepared product is basically the same as that of Example 1 and will not be elaborated here.
[0106] Example 5
[0107] This example is basically the same as Example 1. The main difference is that the aging time is 4 hours.
[0108] The prepared product is basically the same as that of Example 1 and will not be elaborated here.
[0109] Example 6
[0110] This example is basically the same as Example 1. The main difference is that the freeze-vacuum drying time is 18 hours.
[0111] The prepared product is basically the same as that of Example 1 and will not be elaborated here.
[0112] Example 7
[0113] This example is basically the same as Example 2. The main difference is that 100 mg of the molecular sieve-coupled nano-zero-valent iron catalyst prepared in Example 1, 50 mg of deionized water, and 300 mg of 100-mesh walnut shell powder are taken and ground and mixed evenly, and then spread out in the photothermal reactor.
[0114] The reaction product is basically the same as that of Example 2 and will not be elaborated here.
[0115] Example 8
[0116] This example is basically the same as Example 2. The main difference is that the protective gas is nitrogen, and the xenon light source is selected as 6.0 W·cm -2 , and the temperature during the reaction is controlled at not less than 350 °C, and the reaction time is 0.5 hour.
[0117] The reaction product is basically the same as that of Example 2 and will not be elaborated here.
[0118] Example 9
[0119] This example is basically the same as Example 2. The main difference is that the protective gas is nitrogen, and the xenon light source is selected as 2.0 W·cm -2During the reaction, the temperature is controlled at not less than 250 °C, and the reaction time is 2.5 hours.
[0120] The reaction product is basically the same as that of Example 2 and will not be elaborated here.
[0121] The above description of the embodiments is to enable those of ordinary skill in the art to understand and use the invention. It is obvious that those skilled in the art can easily make various modifications to these embodiments and apply the general principles described herein to other embodiments without creative efforts. Therefore, the present invention is not limited to the above embodiments, and all improvements and modifications made by those skilled in the art without departing from the scope of the present invention according to the disclosure of the present invention should be within the protection scope of the present invention.
Claims
1. A walnut shell photothermal conversion method based on molecular sieve coupled nano zero-valent iron, characterized in that: The molecular sieve coupled nano zero-valent iron catalyst and walnut shells were ground and mixed evenly, and then spread flat in a photothermal reactor, and the photothermal reaction was driven by light under a protective atmosphere to convert the walnut shells into phenolic substances; Wherein, the molecular sieve coupled nanometer zero-valent iron catalyst is a micrometer-sized molecular sieve loaded with nanometer zero-valent iron particles.
2. The method for photothermal conversion of walnut shells based on molecular sieve coupled nano zero-valent iron according to claim 1, characterized in that: In the molecular sieve coupled nano zero-valent iron catalyst: The size of the micron-sized molecular sieve is 0.5-3 μm, and the particle size of the nanometer zero-valent iron particles is 1-1000 nm.
3. A walnut shell photothermal conversion method based on molecular sieve coupled nano zero-valent iron according to claim 1 or 2, characterized in that: The molecular sieve coupled nano zero-valent iron catalyst is prepared by the following steps: S1: adding iron source and micron-sized molecular sieve powder into deionized water to form a suspension; S2: Under ultrasonic conditions, NaBH4 solution is added dropwise to the suspension, followed by aging; S3: separating the solid product obtained by the reaction, washing and drying to obtain the molecular sieve coupled nano zero-valent iron catalyst.
4. The method for photothermal conversion of walnut shells based on molecular sieve coupled nano zero-valent iron according to claim 3 is characterized in that: In step S1, The mass ratio of the iron source to the micron-sized molecular sieve is 0.1-10:1; The iron source is a soluble iron-containing compound, and the micron-grade molecular sieve is a 4A type molecular sieve with a mesh size of 200 to 400.
5. The method for photothermal conversion of walnut shells based on molecular sieve coupled nano zero-valent iron according to claim 3, characterized in that: In step S2, The mass ratio of NaBH4 in the NaBH4 solution to the iron source in the suspension is 1.5-5:1; The aging time is 2-5 hours.
6. The method for photothermal conversion of walnut shells based on molecular sieve coupled nano zero-valent iron according to claim 3, characterized in that: In step S3, The separation is suction filtration; The drying is vacuum freeze drying, and the drying time is 12-18 hours.
7. The method for photothermal conversion of walnut shells based on molecular sieve coupled nano zero-valent iron according to claim 1, characterized in that: The mass ratio of the molecular sieve coupled nano zero-valent iron catalyst to the walnut shell is 1:2.5-3; The walnut shell has a mesh size of 100 to 150 and is selected from one or more of Persian walnut shell, iron walnut shell, black walnut shell and hickory shell.
8. A walnut shell photothermal conversion method based on molecular sieve coupled nano zero-valent iron according to claim 1 or 7, characterized in that: Deionized water is also added during the grinding process, and the mass ratio of the deionized water to the walnut shell is 0.5:2.5-3.
9. The method for photothermal conversion of walnut shells based on molecular sieve coupled nano zero-valent iron according to claim 1, characterized in that: The protective atmosphere is nitrogen, argon or water vapor atmosphere.
10. The method for photothermal conversion of walnut shells based on molecular sieve coupled nano zero-valent iron according to claim 1, characterized in that: The photothermal reaction uses a xenon lamp light source to irradiate the mixture, and the light intensity is 0.1 to 6.0 W·cm -2 , the reaction time is 20 to 150 minutes.
Citation Information
Patent Citations
Graphene-water-soluble cellulose photo-thermal film and preparation method thereof
CN118085357A
Hydrogen metallurgy supplementary heating method and device
CN119193955A
Preparation method of hydrogen storage material with CNTs (at) C structure
CN119370832A
Preparation method of photo-thermal biomass cellulose hydrogel
CN119570064A
Solvent-free biomass photo-thermal catalytic conversion method
CN118460224A